History of Gemeente Probolinggo 1918-1942 - Maulana, Afif; Handayani, Sri Ana; Krisnadi, IG (History Education, University of Jember, 2023)
This thesis discusses the history of gemeente Probolinggo in 1918-1942. The problems in this thesis are (1) the reasons why the Dutch East Indies government made Probolinggo a gemeente (2) how was the process of forming gemeente Probolinggo (3) What was the impact of the determination of gemeente on the socio-economic status of Probolinggo. The theory used is public policy theory with a social sociology approach and the method used is the historical method. The factors that made Probolinggo a gemeente by the Dutch East Indies were the strategic location of Probolinggo surrounded by sugar factories, tobacco plantations, coffee and ports. Probolinggo got gemeente status on July 1, 1918 (based on Staatsblad van Nederland Indies 322-1918). The impact of the determination of the Probolinggo gemeente is the development of infrastructure facilities that occur in Probolinggo. the development of infrastructure facilities, among others, such as the development of car and bus transportation. In terms of education also experienced developments, namely initially in Probolinggo there were only two schools then in 1929-1930 in Probolinggo there were 7 schools. From the socio-economic point of view, the majority of the population of Probolinggo are Javanese and Madurese, while the Madurese migrated to Probolinggo due to the opening of plantations by the Dutch East Indies government. Keywords: Gemeente, Development, Infrastructure, Economy, Probolinggo